INDICES OF ACUTE PHASE PROTEINS IN BLOOD SERUM IN PATIENTS WITH VIRAL HEPATITIS A - Kopiychenko, Ya.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Research of the level of acute phase proteins (C-reactive protein, ceruloplasmin, haptoglobin) in 96 patients with viral hepatitis A was conducted in different disease periods. Correlation between the level of acute phase proteins, degree of dysbacteriosis of the large intestine, severity of disease was discovered. It was showed that dynamics of acute phase proteins indices repels morphofunctional liver state. Obtained results of investigation allow using the present indices as ancillary forecasting criterions of viral hepatitis A course.